Flow of Airflow and Pollutant Dispersion Inside an Indoor Space - Anak Johnson, Henry; Lim Ee Kang,; Mark Wong Wizhe,; Muhammad Fauzi Dzuki,; Ishkrizat Taib, (Journal of Advanced Mechanical Engineering Applications, 2026)
In high-occupancy settings like university computer labs, where poor ventilation design can lead to sluggish airflow and dangerous carbon dioxide (CO?) accumulations, maintaining exceptional indoor air quality (IAQ) is a crucial engineering goal. Long-term exposure to such contaminants has a substantial negative influence on staff and students' health and cognitive function. The purpose of this study is to use computational fluid dynamics (CFD) to examine airflow distribution and pollutant dispersion in a computer lab. In particular, the experiment assesses how well ceiling-mounted ventilation devices perform and examines how physical barriers like workstations and hallways affect the efficiency of air exchange. ANSYS Fluent 2025 was used to create a three-dimensional model of a 10 m × 12 m × 3 m laboratory with 33 workstations. The Standard k–? turbulence model was used to simulate steady-state, incompressible, and turbulent airflow, and the species transport model was used to assess CO? dispersion. A Grid Independence Test (GIT) demonstrated that a 500 mm mesh with 71,274 elements provided stable results, achieving a truncation error of only 0.15%. Residuals were tracked until they achieved a convergence threshold of 10-4 to confirm numerical stability. The simulation findings show that room layout and inlet configuration have a significant impact on ventilation effectiveness. As demonstrated by the "Room 3" arrangement, which utilized lateral air dispersion from side-wall units, this configuration emerged as the most effective by providing uniform airflow coverage. It achieved a stabilized peak air velocity of 0.250 m/s, effectively reducing low-velocity "dead zones" and recirculation areas compared to the weaker longitudinal flow in Room 1. These results imply that ventilation systems must be tailored to the specific physical layout of high-density spaces to prevent hazardous pollutant concentrations and ensure a healthy learning environment.